2005
DOI: 10.1073/pnas.0506837102
|View full text |Cite
|
Sign up to set email alerts
|

Dual cancer-specific targeting strategy cures primary and distant breast carcinomas in nude mice

Abstract: Limitations of current viral-based gene therapies for malignant tumors include lack of cancer-specific targeting and insufficient tumor delivery. To ameliorate these problems and develop a truly effective adenovirus gene-based therapy for cancer, we constructed a conditionally replication competent adenovirus (CRCA) manifesting the unique properties of tumor-specific virus replication in combination with production of a cancer-selective cytotoxic cytokine, melanoma differentiation associated gene-7/interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
185
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 117 publications
(189 citation statements)
references
References 51 publications
3
185
1
Order By: Relevance
“…27 The primary antibodies used were anti-BiP/GRP78 (Santa Cruz Biotechnology, Inc, Santa Cruz, CA), anti-Bcl-x L , anti-Bcl-2, PARP (poly(ADP-ribose) polymerase-1), p38 MAP (mitogenactivated protein) kinase, p-p38MAP kinase, ERK Human prostate cancer xenografts in athymic nude mice DU-145 and PC-3 cells (3 Â 10 6 ) were injected subcutaneously in 100 ml of PBS in the left flank of male athymic nude mice (NCRnu/nu, 4 weeks of age, 20 g body weight). 27,28 After establishment of visible tumors of B75 mm 3 , requiring approximately 8-10 days, intratumoral injections of different Ads were administered only to tumors on the left flank at a dose of 4.5 Â 10 8 p.f.u. (plaqueforming units) in 100 ml.…”
Section: Methodsmentioning
confidence: 99%
“…27 The primary antibodies used were anti-BiP/GRP78 (Santa Cruz Biotechnology, Inc, Santa Cruz, CA), anti-Bcl-x L , anti-Bcl-2, PARP (poly(ADP-ribose) polymerase-1), p38 MAP (mitogenactivated protein) kinase, p-p38MAP kinase, ERK Human prostate cancer xenografts in athymic nude mice DU-145 and PC-3 cells (3 Â 10 6 ) were injected subcutaneously in 100 ml of PBS in the left flank of male athymic nude mice (NCRnu/nu, 4 weeks of age, 20 g body weight). 27,28 After establishment of visible tumors of B75 mm 3 , requiring approximately 8-10 days, intratumoral injections of different Ads were administered only to tumors on the left flank at a dose of 4.5 Â 10 8 p.f.u. (plaqueforming units) in 100 ml.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] These findings were extended to human-tumor xenograft nude mouse models, indicating that Ad.mda-7 suppresses tumor growth and cancer progression. [18][19][20][21][22] Through studies in multiple laboratories, it is now eminently clear that mda-7/IL-24 is one of the broadest-acting, cancer-specific and apoptosis-inducing cytokine genes, which also displays antiangiogenic, radiosensitizing, immune-stimulating and potent 'bystander' antitumor activity. [17][18][19][20][21][22][23][24][25][26] A momentous step in the evolution of mda-7/IL-24 as a potential therapeutic gene was the evaluation of Ad.mda-7 (INGN 241) in a phase-I clinical trial by intratumoral injection in patients with advanced solid tumors, including melanomas.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] Through studies in multiple laboratories, it is now eminently clear that mda-7/IL-24 is one of the broadest-acting, cancer-specific and apoptosis-inducing cytokine genes, which also displays antiangiogenic, radiosensitizing, immune-stimulating and potent 'bystander' antitumor activity. [17][18][19][20][21][22][23][24][25][26] A momentous step in the evolution of mda-7/IL-24 as a potential therapeutic gene was the evaluation of Ad.mda-7 (INGN 241) in a phase-I clinical trial by intratumoral injection in patients with advanced solid tumors, including melanomas. 13,16,18,[27][28][29] These studies indicated that mda-7/IL-24 was safe and could induce as much as 70% apoptosis in tumors following a single injection of recombinant virus, and with multiple injections, it promoted objective clinical responses, especially in melanoma patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations